Digital Maslahah in Higher Education: Communicating Transformational Leadership through Implicit Islamic Ethics - Dhita Widya Putri; Aditya Nugroho Pratomo; Taufan Teguh Akbari (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2025)
This research explores how university leaders employ transformational styles of Islamic leadership and migration ethics, and how such leaders in Islamic higher education navigate crisis. Using qualitative methods and a case study design, data were collected through semi-structured interviews with four strategic leaders from private universities in the Greater Jakarta Area. The findings demonstrate the emergence of